Pembelajaran IPS Kurikulum Merdeka SMP-SMA - Hutabarat, Cindy Adelina O; Erdo, Dio Fani (PT. LANCAR MEDIA KOMUNIKASI, 2023)
Curiculum development very influential in the learning process of students, so that they can achieving social studies learning objectives at the elementary, junior high and high school levels. Current curriculum development, namely the independent curriculum is considered very appropriate because the learning process adjusts to the level understanding of each student, because the author understands that the ability of each learner to absorb learning material different, so the teacher cannot use one method the same learning for all students. That way the teacher will be more aesy to achieve social studies learning studies learning objectives. Based on this, it can be seen that the curriculum independent learning includes character education that can be applied to social studies learning. Even in the curriculum merdeka learn this IPS is combined with science subjects so that be an IPA, but does not reduce the ability of teacher in implementing is necessary for teacher to be able to incorporate character values in the learning. Policy breakthrough independent learning policy, has its own purpose where the unit education or schools, teacher and students have the freedom to innovate, learn independently and be creative.